A STUDY ON FINANCIAL PERFORMANCE EVALUATION OF SELECTED TEXTILE COMPANIES IN INDIA: AN EMPRICAL ANALYSIS - Dr Sugandha Chhibber (Research Parks Publishers, 2020)
The Indian textile industry is one of the largest in the world after China with a massive raw material and textiles manufacturing base. This sector has played a pioneered role in growth and upliftment of country. This sector has contributed seven per cent of the industry output (in value terms) of India in 2018-19. This sector has generated employment for more than 45 million people, and further this contributed fifteen percent share to the country’s export. It contributed seven per cent to the GDP of India and employs more than 45 million people in 2018-19. Apparel constituted for around three-fourth of the total textile and apparel market in India. Presently, Indian textile sector is growing at a rapid pace and is getting international recognition. Indian domestic textile and apparel market was US 100 billion in 2018-19, which is expected to grow to US 220 billion by 2025 at a CAGR of 12%. This sector is also taking adequate measures for the development of export oriented products, attracting new investments both domestic and foreign. Besides this sector has significant importance of employment generation, industrial, social and economical in nature. Further each company could invest on the basis of current performance compared with previous year or with other company. Decision making, additional investment, liquidity position changes in working capital depend upon the performance & return of company reports. Funds are highly required for day-to-day business operations of the firm and how to utilize it and in what way should avoid loses from the investment are discussed here plus, it happens by ineffective management. Hence the present study aims to analyze the financial performance of textile industry in the selected Indian companies. In addition, the data is collected from the CMIE and used the tools of ANOVA and descriptive statistics. This study results would help the shareholders, the investors, policymakers, managers, researchers and people who are involved in financial decision